Generation of sequence-specific, high affinity anti-DNA antibodies. - Cerutti, Maria Laura (2001)
By taking advantage of the extreme stability of a protein-DNA complex, we have obtained two highly specific monoclonal antibodies against a predetermined palindromic DNA sequence corresponding to the binding site of the E2 transcriptional regulator of the human papillomavirus (HPV-16). The purified univalent antibody fragments bind to a double-stranded DNA oligonucleotide corresponding to the E2 binding site in solution with dissociation constants in the low and subnanomolar range. This affinity matches that of the natural DNA binding domain and is severalfold higher than the affinity of a homologous bovine E2 C-terminal domain (BPV-1) for the same DNA. These antibodies discriminate effectively among a number of double- and single-stranded synthetic DNAs with factors ranging from 125- to 20,000-fold the dissociation constant of the specific DNA sequence used in the immunogenic protein-DNA complex. Moreover, they are capable of fine specificity tuning, since they both bind less tightly to another HPV-16 E2 binding site, differing in only 1 base pair in a noncontact flexible region. Beyond the relevance of obtaining a specific anti-DNA response, these results provide a first glance at how DNA as an antigen is recognized specifically by an antibody. The accuracy of the spectroscopic method used for the binding analysis suggests that a detailed mechanistic analysis is attainable.